PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI KAHOOT DALAM MENINGKATKAN HASIL BELAJAR IPAS MATERI GAYA DISEKITAR KITA KELAS IV MINU TROPODO WARU SIDOARJO - Muhammad Alif; Nur Wakhidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low academic achievement of students in the subject of Natural and Social Sciences (IPAS), particularly on the topic “Forces Around Us” in Grade IV at MINU Tropodo Waru Sidoarjo. Initial observations revealed that most students struggled to understand the concepts of muscular force, friction, gravity, and magnetism, as well as showed a lack of active engagement during the learning process. One contributing factor is the use of conventional teaching methods, which tend to be monotonous and less engaging for students. Therefore, this study aims to analyze the effect of interactive learning media based on the Kahoot application on improving IPAS learning outcomes in the topic of forces. The research employed a quasi-experimental method with a pretest-posttest control group design. The study involved two classes as samples: class IV-A as the experimental group using Kahoot media, and class IV-B as the control group using the lecture method. The instrument used was a multiple-choice test consisting of 10 validated items. Data were analyzed using Normality, Homogeneity, and Paired Sample t-Test through SPSS version 26. The results showed that the average posttest score of students in the experimental group increased significantly compared to the control group. The mean posttest score of the experimental group was 77.68, while the control group only reached 57.50. The Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the two groups. These findings demonstrate that the use of Kahoot as an interactive learning medium can effectively enhance students’ IPAS learning outcomes. This study recommends the use of Kahoot as an innovative and enjoyable teaching strategy to support the implementation of the Merdeka Curriculum at the elementary school level.